Development of a sealed MRPC with mylar spacers for high luminosity TOF systems - Wang, Botan; Sun, Kai; Wang, Yi; Han, Dong; Deppner, Ingo Martin; Herrmann, Norbert; Guo, Baohong; Chen, Xiaolong; Liu, Daming; Zhang, Qiunan (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2023)
The high luminosity Time-of-Flight (TOF) systems call for timing detectors with both good time resolution and adequate rate capability, which have been fulfilled by the Multigap Resistive Plate Chamber (MRPC) assembled with low-resistive glass electrodes. However, recent tests and operations with high rate MRPCs have given evidences to the luminosity effects, such as the dark current rise and related higher noise rate, which may vitiate the stability in experimental operations. This work discusses the results from observations and tests, and infer the fishline spacers as a source of dark current and noise problems. Then, a sealed MRPC with mylar spacers is proposed, developed and tested. The prototype showed good luminosity tolerance during the X-ray test, and its performances of 95% efficiency and 80 ps time resolution have been validated in cosmic tests.